ANALISIS SISTEM PENGUPAHAN PABRIK TAHU DI POLUJU BAURENO BOJONEGORO DITINJAU DARI PRINSIP TANGGUNG JAWAB DALAM EKONOMI ISLAM - Misbahul Khoir; Yusri Naili (Akademika, 2018)
The provision of wages to all employees or workers is very important to prosper the surrounding community. One of them is the tofu factory in the village of Poluju, Baureno sub-district, Bojonegoro regency, which is one of the factories producing tofu from the processed soybean staple. The research problems are how analyze the wage system of tofu factory employees in Poluju village, Baureno sub-district, Bojonegoro regency; what is the analysis of the tofu factory employee wage system viewed from the principle of responsibility in Islamic economics by using descriptive qualitative research methods. Data collection techniques are through observation, interviews, and documentation. The data analysis technique uses Miles and Huberman. In this tofu factory, Mr. Sukanto uses a daily and piece rate system. Where both systems have been running from the founding of the Sukanto tofu factory to the present. In determining the wage, it is known by both parties, namely the employees and manager. In giving the salary, Mr. Sukanto is quite responsible because he has fulfilled several principle  criteria of responsibility in Islamic economics. the principle criteria for responsibility in Islamic economics, are honesty, trustworthy, open to each other, and taking full responsibility for the wages of all employees.